Roost selection of the short-nosedfruit bat, Cynopterusspp. in Sri Lanka - Digana, P.M.C.Bandara; Yapa, Wipula B; Randeniya, Preethi V; Ratnasooriya, W.D (Journal of Science of the University of Kelaniya, Sri Lanka, 2003)
A total of 160 days of short nosed fruit bats (Cynopterus sp) were examined during a 3 years study in Sri Lanka. Day roosts were found in five species of trees; Talipot palm (Corypha umbraculifera), coconut (Cocos nucifera), Banan found in this study can be categorized in to three groups, viz, tents, fliage roosts, and seed string roosts. Majority (92%) of day roosts were in the form of tents, all of which were found in the talipot palm. Foliage roosts (7%) were found in three species of plants (C.nucifers, Musa sp, Alocasia sp) while two (1%) of the roosts were found in of Kithul palm, inside the seed string. Our observations indicate that the tents are constructed by male bats and serve as the primary roosts of the Cynopterus.
Keywords: Cynopterus; Chiroptera; day roosts; tents; Corypha umbraculifera